(untitled) (International Journal of Engineering and Computer Science, 2014)
Air is a cheap and safe fluid, widely used in electronic, aerospace and air conditioning applications. Because of its poor heat transfer properties, it always flows through extended surfaces, such as finned surfaces, to enhance the convective heat transfer. In this paper, experimental results are reviewed and numerical studies during air forced convection through extended surfaces are presented. The thermal and hydraulic behaviors of a reference trapezoidal finned surface, experimentally evaluated by present authors in an open-circuit wind tunnel, has been compared with numerical simulations